Use of anti-B-cell therapy in case of antisynthetase syndrome as the severest subtype of polymyositis/dermatomyositis - O A Antelava; A N Khelkovskaia-Sergeeva; G M Tarasova; N Iu Nikishina; N E Lopatina; S G Pal'shina; T P Fedina; E G Sazhina (Терапевтический архив, 2014)
Antisynthetase syndrome encompassing a symptom complex with severe interstitial lung disease is the severest subtype of polymyositis and dermatomyositis. The characteristic feature of antisynthetase syndrome is the insufficient efficiency of traditional therapy with glucocorticosteroids and cytostatics, which determines the prognosis of the disease and the need for new therapeutic approaches to treating these patients.